POWER AND BUSINESS IN THE WESTERN WORLD: TRANSFORMATION OF RELATIONS AT THE TURN OF THE ХХ-ХХІ CENTURIES - Зайдель, М.І. (The Journal of V.N. Karazin Kharkiv National University. Series "Issues of Political Science", 2012)
Specifics of cooperation between power and business in the Western world in the process of global social changes determining of domination of neoliberal doctrine are analyzed. It is examined the mechanisms of partnership between state and private sector for achievement  of public goods. The challenges for democracy as a result of approaching power resource and potency of corporation are underlined.